From Extremism to Moderation: Examining the Impact of the Densus 88 Assistance Program on Ex-Terrorism Convicts in Cirebon, West Java - Hidayatulloh, Taufik; Alam, Rudy Harisyah; Rahman, Zaizul Ab. (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
This study examines the influence of Indonesia's Counterterrorism Special Detachment 88 unit (Densus 88 AT) assistance program on former terrorism convicts in Cirebon Regency, West Java, focusing on changes in their religious beliefs and attitudes. With security concerns surrounding violent extremism and terrorism in Indonesia, this research addresses the challenge of managing terrorism convicts who have completed their sentences, given the significant number of former terrorist offenders in certain regions. Using a case study approach, the research employs narrative analysis to collect primary data through observations, interviews, and a literature review. The fieldwork occurred in two phases between February and May 2021, involving former terrorism convicts, Densus 88 AT personnel, and Ministry of Religious Affairs officials. The study’s findings demonstrate shifts in socio-religious beliefs among the four informants, moving from extremist takfiri views to more moderate perspectives. Their paths to radicalization were diverse, influenced by groups like JAD and NII. The research highlights prisons as spaces for both radicalization and deradicalization, with interactions and exposure to alternative knowledge influencing changes in religious views. While Densus 88 AT’s economic recovery activities did not directly impact religious beliefs, they fostered attitudes conducive to religious interventions, such as flexible thinking and positive emotional attitudes. The study recommends involving religious leaders and educators to support economic recovery initiatives and promote a more moderate religious outlook among former terrorists. Enhanced collaboration among stakeholders is crucial to reinforce and effectively implement such programs, particularly with many terrorism convicts nearing the end of their sentences.